СORTICOSTEROIDS AS MEAN OF NOSOTROPIC THERAPY OF TUBERCULOSIS - Кulish, М.V. (World of Medicine and Biology, 2013)
In the review it is marked, that corticosteroids, which are appointed additionally to standard therapy of tuberculosis, assist the increase of efficiency of treatment and decrease drag sides effects on antituberculous drags. Most effective is a chart of setting of corticosteroids taking into account the biorhythm of function of adrenal glands.
Keywords: tuberculosis; corticosteroids; efficiency of setting